Building resilience through group visual arts activities: Findings from a scoping study with young people who experience mental health complexities and/or learning difficulties. (September 2016) - Macpherson, Hannah; Hart, Angie; Heaver, Becky
Summary: This article reports research that aimed to identify and evaluate potential resilience benefits of visual arts interventions for young people with complex needs. The study involved a review of the 'arts for resilience' literature and a case study of 10 weekly resilience-building arts workshops for 10 young people experiencing mental health complexities and/or learning difficulties. Findings: We found a significant existing evidence-base linking visual arts practice to individual and community resilience, across disciplinary fields including art therapy, social work, community health, visual arts practice and geographies of health. Visual art activities were utilised to both educate young people about resilience and enhance young people's overall resilience. Qualitative research material developed from the case study shows that even short-term visual arts interventions can impact on young people's resilience – crucially, participation was extremely beneficial to young people's sense of belonging and ability to cope with difficult feelings (topics which arose repeatedly during interview, focus group discussion and observation). Applications: Our review and findings from this small case study provide some initial insights into the resilience benefits of participation in visual arts activities. This, combined with the resilience-based practice framework presented here, could aid the effective targeting of interventions for social workers and others working with young people with complex needs. Alongside this research paper, an arts for resilience practice guide has been produced by the project team (including young people). It contains instructions on how to conduct a range of practical visual arts activities that we identified as being resilience-promoting.